Power dissipation of an inductively coupled plasma torch under E mode dominated regime - Yu, Nan; Jourdain, Renaud; Gourma, Mustapha; Xu, Fangda; Bennett, Adam; Fang, Fengzhou (MDPI, 2021)
This paper focuses on the power dissipation of a plasma torch used for an optical surface fabrication process. The process utilizes an inductively coupled plasma (ICP) torch that is equipped with a De-Laval nozzle for the delivery of a highly collimated plasma jet. The plasma torch makes use of a self-igniting coil and an intermediate co-axial tube made of alumina. The torch has a distinctive thermal and electrical response compared to regular ICP torches. In this study, the results of the power dissipation investigation reveal the true efficiency of the torch and discern its electrical response. By systematically measuring the coolant parameters (temperature change and flow rate), the power dissipation is extrapolated. The radio frequency power supply is set to 800 W, E mode, throughout the research presented in this study. The analytical results of power dissipation, derived from the experiments, show that 15.4% and 33.3% are dissipated by the nozzle and coil coolant channels, respectively. The experiments also enable the determination of the thermal time constant of the plasma torch for the entire range of RF power.
Keywords: heat transfer; plasma processing; inductively coupled plasma